2015
DOI: 10.1002/ps.4004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CO2dissolution on phase distribution and degradation of dimethyl disulfide in soils under grape production

Abstract: While trials are needed for validation of field-scale impacts, carbonation had mixed effects on soil partitioning and no discernable impact on degradation, but greatly decreased DMDS water solubility. This indicates that carbonation could improve some facets of DMDS diffusion and dispersion, depending on soil properties (carbon content and moisture), without greatly affecting its other behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…DMDS exhibits great insecticidal and fungicidal activities in vitro study[4, 5]. And DMDS is highly efficient in controlling many soilborne diseases and nematodes of numerous crops, such as tomato[6], cucumber[7], strawberry[8] and other crops [9, 10]. This fumigant also provides good control on yellow nutsedge [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…DMDS exhibits great insecticidal and fungicidal activities in vitro study[4, 5]. And DMDS is highly efficient in controlling many soilborne diseases and nematodes of numerous crops, such as tomato[6], cucumber[7], strawberry[8] and other crops [9, 10]. This fumigant also provides good control on yellow nutsedge [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…For best performance, the fumigant must move across the soil profile and last an appropriately long time to ensure successful soil pest control [18,19]. Conkle et al [20] reported that DMDS might need to be applied at a high dose to achieve higher efficacy due to its lower volatility and higher soil adsorption rate. However, soils with high fumigant concentrations can cause phytotoxicity, which usually results in low yields or even plant death.…”
Section: Introductionmentioning
confidence: 99%